2018
DOI: 10.1021/acs.jpclett.8b00825
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Internal Friction and Structural Constraints for the Dynamics of Denatured Bovine Serum Albumin

Abstract: A general property of disordered proteins is their structural expansion that results in a high molecular flexibility. The structure and dynamics of bovine serum albumin (BSA) denatured by guanidinium hydrochloride (GndCl) were investigated using small-angle neutron scattering (SANS) and neutron spin-echo spectroscopy (NSE). SANS experiments demonstrated the relevance of intrachain interactions for structural expansion. Using NSE experiments, we observed a high internal flexibility of denatured BSA in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 17 publications
5
34
0
Order By: Relevance
“…The effect of chemical denaturation on BSA at lower concentrations (∼30 mg ml −1 ) induced by 6 M guanidinium hydrochloride (GndCl) at T = 295 K was studied with TOF and NBS by Ameseder et al (2018aAmeseder et al ( , 2018b. Moreover, also the effect of the reduction of disulfide bridges in denatured BSA induced by 6 M GndCl 150 mM β-mercaptoethanol (β-met) was investigated.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of chemical denaturation on BSA at lower concentrations (∼30 mg ml −1 ) induced by 6 M guanidinium hydrochloride (GndCl) at T = 295 K was studied with TOF and NBS by Ameseder et al (2018aAmeseder et al ( , 2018b. Moreover, also the effect of the reduction of disulfide bridges in denatured BSA induced by 6 M GndCl 150 mM β-mercaptoethanol (β-met) was investigated.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Anmentioning
confidence: 99%
“…The additional reduction of disulfide bridges in the denatured protein was found to lead to only a slightly increased flexibility. However, a later NSE study by Ameseder et al (2018a) indicated that presence of the sulfur bonds leads to a suppression of low-frequency Zimm modes (see section 'Relations of protein dynamics to structure: from globular to intrinsically disordered proteins'). Although incapable of distinguishing heterogeneous dynamics on the same timescale, as the authors noted (Ameseder et al, 2018b), the Brownian oscillator model yielded reasonably similar results with D fast int = 95.8 + 1.8 Å 2 ns −1 and D slow int = 24.5 + 1.5 Å 2 ns −1 in the native protein and diffusion coefficients between 14 and 21 Å 2 ns −1 in denatured BSA.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Anmentioning
confidence: 99%
“…119 Neutron spin echo spectroscopy 120 may be the only other method besides nsFCS currently available for probing (bio)polymer chain dynamics in the tens of nanosecond range; it can reveal a large spectrum of relaxation modes and has been used to identify internal friction. 121,122 Arguably the most popular technique for IDPs is nuclear magnetic resonance (NMR) spectroscopy: While the time scales of global chain dynamics are difficult to access with NMR because of rotational decorrelation, the technique is ideal for obtaining a wealth of information on local dynamics, especially on the level of individual residues or segments forming secondary structures. 123,124 With such combined data acting as stringent benchmarks or restraints, it should ultimately be possible to use the framework of MD simulations to describe the complete structural and dynamic properties of unfolded and intrinsically disordered proteins from picoseconds to microseconds and beyond.…”
Section: Integration Of Methodsmentioning
confidence: 99%
“…1 (a)), subjected to fluctuating random forces from the bath of solvent molecules it is immersed in. This model has been widely invoked in rheological, 1,[29][30][31] as well as biophysical contexts, 6,12,32 to capture the effects of internal friction in polymers. Within this model, the spring accounts for the entropic elasticity in the polymer molecule, whereas the dissipative effect from the myriad sources of internal friction is captured by the dashpot.…”
Section: Introductionmentioning
confidence: 99%